Медицинский туризм как фактор развития туризма в России - Зульфия, Хамадеева (Вестник ЗКУ, 2023)
Medical tourism is gaining more and more strong positions in the economic space. The flow of those wishing to receive highly qualified medical care at affordable prices, and at the same time broaden their horizons, is increasing. The amount of funds spent on health improvement is increasing, and the market for medical tourism services is growing accordingly. The main aspects of tourism development in the Russian Federation are considered, problems and prospects are defined. In the Russian Federation, there are prospects, growth potential in the field of medical tourism, no matter what. International tourism in the world is developing. It is clear that this direction is generally promising, and taking into account the level of prices and the acceptable quality of medical services provided, it is the same in our country. The level of infrastructure development, the presence of medical institutions, world-famous doctors, the construction of new medical centers and research institutes, the creation of a vaccine against a new virus, allow us to talk about growth points for medical tourism. Particular interest can be expected from the nearest neighbors, in which the level of development of medicine is lower.